Dimensions of hospital workplace violence: Patient violence towards the healthcare team. Issue 11 (29th August 2021) - Chesire, David J.; McIntosh, Ana; Hendrickson, Susan; Jones, Patrice; McIntosh, Mark
Abstract: Aims and Objectives: To investigate the cognitive dimensions nurses use when perceiving patient‐to‐healthcare provider workplace violence. Background: The concept of workplace violence, especially with respect to healthcare settings, has been well documented. Healthcare workers are at particular risk for experiencing violence from their patients, though these incidents often go unreported. Experiencing violence in the workplace has been associated with numerous negative outcomes, including absenteeism, burnout and diminished quality of care. However, little emphasis has been placed on understanding the concept of violence itself, or why one type of violence might go unreported whilst another is readily communicated to officials. Design: A card‐sorting, multidimensional scaling design. Methods: Thirty two nurses completed the card‐sorting task. Using multidimensional scaling (MDS), 75 reported incidents of violence were considered. SPIRIT research reporting checklist followed. Results: Nurses categorise patient violence in three dimensions: physical versus verbal, active versus threatening and more versus less severe. Implications for further research and intervention are discussed. Conclusions: Violence in the hospital workplace is a complex perception by the healthcare worker that cannot be captured by a single dimension. Relevance to clinical practice: This study provides a theoretical framework for understanding the complexity of patient‐to‐provider violence in a hospital setting. It sheds light on why only a minority of such events are reported. This model can serve as a foundation for future research exploring interventions for hospital violence.